WNT16 antagonises excessive canonical WNT activation and protects cartilage in osteoarthritis. Issue 1 (4th May 2016) - Nalesso, Giovanna; Thomas, Bethan Lynne; Sherwood, Joanna Claire; Yu, Jing; Addimanda, Olga; Eldridge, Suzanne Elizabeth; Thorup, Anne-Sophie; Dale, Leslie; Schett, Georg; Zwerina, Jochen; Eltawil, Noha; Pitzalis, Costantino; et al.
Abstract : Objective: Both excessive and insufficient activation of WNT signalling results in cartilage breakdown and osteoarthritis. WNT16 is upregulated in the articular cartilage following injury and in osteoarthritis. Here, we investigate the function of WNT16 in osteoarthritis and the downstream molecular mechanisms. Methods: Osteoarthritis was induced by destabilisation of the medial meniscus in wild-type and WNT16-deficient mice. Molecular mechanisms and downstream effects were studied in vitro and in vivo in primary cartilage progenitor cells and primary chondrocytes. The pathway downstream of WNT16 was studied in primary chondrocytes and using the axis duplication assay in Xenopus. Results: WNT16-deficient mice developed more severe osteoarthritis with reduced expression of lubricin and increased chondrocyte apoptosis. WNT16 supported the phenotype of cartilage superficial-zone progenitor cells and lubricin expression. Increased osteoarthritis in WNT16-deficient mice was associated with excessive activation of canonical WNT signalling. In vitro, high doses of WNT16 weakly activated canonical WNT signalling, but, in co-stimulation experiments, WNT16 reduced the capacity of WNT3a to activate the canonical WNT pathway. In vivo, WNT16 rescued the WNT8-induced primary axis duplication in Xenopus embryos. Conclusions: In osteoarthritis, WNT16 maintains a balanced canonical WNT signalling and prevents detrimental excessive activation, thereby supporting the homeostasis of progenitor cells.